2020
DOI: 10.3126/jnps.v40i1.28460
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunological Spectrum of Systemic Lupus Erythematosus in Children

Abstract: Introduction: Systemic Lupus Erythematosus (SLE) is an auto immune disorder affecting mainly adolescent females and young women of reproductive age. The disease is characterised by widespread inflammation of blood vessels and connective tissues due to the presence of anti-nuclear antibodies (ANA). There are limited number of studies from South India on paediatric lupus. Our objectives were to study the clinical and immunological features of childhood SLE along with treatment modalities and its outcome at the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(29 reference statements)
2
3
0
Order By: Relevance
“…The mean value of the age, at diagnosis, was 12.91±1.94 years in our study. These results were not different from those demonstrated by Kini et al 18 and Gomes et al 19…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The mean value of the age, at diagnosis, was 12.91±1.94 years in our study. These results were not different from those demonstrated by Kini et al 18 and Gomes et al 19…”
Section: Discussionsupporting
confidence: 54%
“…The mean value of the age, at diagnosis, was 12.91±1.94 years in our study. These results were not different from those demonstrated by Kini et al 18 and Gomes et al 19 Musculoskeletal manifestation were the most prevalent clinical characteristics found in among those patients, in the form of polyarthralgia (71%), followed by haematological manifestations (65%), malar rash (54%), nephritis (51%), and neuropsychiatric manifestations (27%). Similar results were obtained by different studies by Torrente-Segarra et al and Kosaraju et al who found that musculoskeletal manifestations were the most frequent clinical characteristics (77.9%, 64.8%) respectively.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…One needs to be cautious in comparing studies as definition of treatment response and proteinuria in various previous studies has been variable. [18][19][20][21][22][23][24][25][26] Similar to the prospective German registry by Suhlrie et al 17 we quantified proteinuria as per 24 h estimation normalized to body surface area (BSA) and used the KDIGO 2021 definition for cut-off. 36 Others used spot urine protein creatinine ratio 26 or even a fixed cut-off without adjusting for age or size.…”
Section: Discussionmentioning
confidence: 99%
“…9 Due to the scarcity of published pediatric cohorts, especially from diverse ethnic and healthcare settings, [10][11][12][13][14][15][16][17] the management of childhood LN have been primarily extrapolated from mainly adult studies from high resource Western countries. Childhood LN may affect South Asian children differently but a literature search found only few representative cohorts with most of the studies reported from a bygone era (Supplementary Table 1) [18][19][20][21][22][23][24][25][26] when mycophenolate mofetil (MMF) and biologics were not commonly used.…”
Section: Introductionmentioning
confidence: 99%